Siemens Strategy to Have a Leap Growth on In-Vitro Diagnostic (IVD) Business in Indonesia - Reza, Kemal; Marimba, Percy (The Indonesian Journal of Business Administration, 2012)
Healthcare Diagnostic Industry in Indonesia is showing promising growth by the time. As one of the emerging countries that have the largest population in South East Asia that makes Indonesia is categorized as second wave emerging countries. Healthcare Diagnostic is one of the business divisions of Healthcare Sector PT. Siemens Indonesia. The potential, unique business behavior and niche market attracts managementÃ¢â‚¬â„¢s attention to seriously develop the business since PT. Siemens Indonesia as principal was handing over the business on 2011.Division of healthcare diagnostic has officially become a division of PT. Siemens Indonesia Ã¢â‚¬â€œ Healthcare Sector in 2011. Grow the business on a leap is the main target from handing over business process to Siemens Indonesia. Therefore, it required accurate business strategy to meet the demand and to compete with competitors so that Siemens could develop and achieve the growth on a Ã¢â‚¬Å“leapÃ¢â‚¬Â.To determine the precise business strategy, the writer will require strategic analysis that includes external and internal. Business strategy developed should be derived down to business model and business tactic to give detail description of the steps taken and determine percentage numbers of Ã¢â‚¬Å“leapÃ¢â‚¬Â growth to be achieved within five years from the implementation of the business strategy. Keywords: business strategy, leap growth, market analysis.